Understanding the Ethical Attitude-behavior Gap in Consumption: A Shred of Empirical Evidence from Nepal - Budhathoki, Pragya; Devkota, Niranjan; Mahapatra, Sushanta Kumar; Paudel, Udaya Raj; Bhandari, Udbodh; Parajuli, Seeprata (Journal of Development and Administrative Studies, 2021)
This paper explores factors impeding the ethical consumption of grocery products in the Nepalese context, which will enhance our understanding of various socio-psychological aspects of consumer behavior. Moreover, this paper explores the existing cavity between ethical consumption intentions and consumers' actual purchasing conduct. This study is based on an explanatory research design, including both primary and secondary data. In this study, the population represents consumers' shopping grocery products in Big Marts, and 270 consumers have been selected as the sample. We have used the awareness index to study the ethical consumption of grocery products in Nepal to reduce the errors associated with lying. Empirical results reveal that the surveys and research on value-based consumption, constructing an instrument of questions, socio-political statements, and behaviors that, through item analysis and data reduction, can categorize a respondent as an "ethical consumer," or a "utilitarian consumer" could reduce the loopholes created by respondent lies in the studies. Results of the awareness index depicts that more than ninety percent Big Mart’s grocery consumers are moderately aware about ethical consumption. The regression result indicates that random product selection is an impending factor towards ethical consumption. Respondents were found to be less concerned about ethical consumption towards a certain brand. The result of this study will help to enhance our understanding on various socio-psychological aspects of consumer behavior. From the policy prescription standpoint, this study provides direction for the researcher to conduct analyses related to consumer understanding of ethical consumption and their purchasing behavior in Nepal.